2021
DOI: 10.3389/fcell.2021.636802
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone-Regulated Expression of Period2 Promotes Liver Urate Production

Abstract: The relationship between thyroid hormones and serum urate is unclear. Our aim is to analyze the correlation between uric acid and thyroid hormones in gout patients and to explore the effect and mechanism of triiodothyronine on liver uric acid production. Eighty men patients with gout were selected to analyze the correlation between blood urate and thyroid function-related hormone levels. Stepwise multiple linear regression was used to analyze factors affecting blood urate in patients with gout. Levels of urate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…[ 34 ] Studies have shown that T3 can affect the levels of enzymes involved in nucleotide metabolism in the liver and promote urate production by inducing Per2 expression, revealing a potential mechanism between thyroid disease and gout. [ 35 ] In addition, thyroid hormones can affect kidney development, kidney structure, and glomerular filtration rate. Hyperthyroidism and hypothyroidism are one of the key factors affecting renal function.…”
Section: Discussionmentioning
confidence: 99%
“…[ 34 ] Studies have shown that T3 can affect the levels of enzymes involved in nucleotide metabolism in the liver and promote urate production by inducing Per2 expression, revealing a potential mechanism between thyroid disease and gout. [ 35 ] In addition, thyroid hormones can affect kidney development, kidney structure, and glomerular filtration rate. Hyperthyroidism and hypothyroidism are one of the key factors affecting renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical assay was performed as previously described ( 28 ) using anti-PRPS1 (Proteintech, #15549-1-AP), anti-NRF2 (Abcam, ab89443) and anti-(Proteintech, #15549-1-AP) antibodies. Tissue microarrays (MME1004i) were purchased from xi,an Taibosi Biological Technology Co., Ltd. (Xian, China).…”
Section: Methodsmentioning
confidence: 99%
“… 24 The investigator observed elevated UA in HepG2, Hep1-6 cell and mouse liver treated by T3, further making clear that T3 regulates nucleotide metabolizing enzyme partially through Pre2 expression mediated by TR-β. 25 The hypermetabolic state associated with hyperthyroidism leads to an increased production of UA, surpassing its clearance capacity and resulting in the development of hyperuricemia ( Figure 1 ).…”
Section: Pituitary-thyroid Axismentioning
confidence: 99%